Análise de desempenho econômico de municípios gaúchos emancipados - Marengo, Sabrina Trejes (Universidade do Vale do Rio dos Sinos, 2012)
The present study aims to analyze the socio-economic performance of cities in the state emancipated and their municipalities of origin. The sample was defined for the last emancipatory movement occurred in the state of Rio Grande do Sul. The field consists of 66 municipalities comprising 25 towns emancipated in 1996 (installed in 2001) and its 41 municipalities of origin. The performance of the municipalities of origin is analyzed based on the years preceding the date of emancipation or in pre-emancipation period corresponds to 2000, and in post-emancipation, in 2009 and 2010. Used variables that can be applied any municipality regardless of the size of its population, location or geographic area. The indicators and selected variables were collected from the databases of the Secretaria do Tesouro Nacional (STN), Fundação de Economia e Estatística do RS (FEE-RS) and the Instituto Brasileiro de Geografia e Estatística (IBGE). The analysis revealed that the municipalities had emancipated performances inferior to theirs cities of origin in all indicators. Regarding the performance of revenue 92% of municipalities have their own income emancipated negative, which reflects in an almost total dependence of the funds transferred by the State and Union profile analysis of spending by municipalities emancipated revealed that the sum of the percentage paid on education, health, culture, sanitation, housing, urbanization and the legislative function is less than the sum of the percentage paid by the municipalities of origin. With respect to the financial and socioeconomic municipalities had emancipated mostly lower performance on all indicators, and with respect to any of the municipalities IDESE emancipated superior performance to its city of origin. The test of mean difference indicates no significant differences between the mean of the variables of emancipated municipalities and counties of origin.
Keywords: Gestão pública; Emancipação de municípios; Desempenho econômico; Public management; Emancipation of municipalities; Socioeconomic performance; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis